Ic(q)-convergence of arithmetical functions - Gogola, Ján; Baláž, Vladimír; Visnyai, Tomáš (Academic Press (Elsevier), 2018)
The statistical convergence is equivalent with Id-convergence, where Id is the ideal of all subsets of positive integers having the asymptotic density zero. In this paper we will study I-convergence of well known arithmetical functions, where I=Ic(q) is an admissible ideal on N for q in ]0,1] such that Ic(q) is a proper subset of Id.
Ic(q)-konvergence aritmetických funkcí
Keywords: ideal covergence, arithmetical functions; ideálová konvergence, aritmetické funkce